Assessing effects of scanner upgrades for clinical studies. Issue 6 (21st May 2019) - Keenan, Kathryn E.; Gimbutas, Zydrunas; Dienstfrey, Andrew; Stupic, Karl F.
Abstract : Background: Scanner upgrades due to software and hardware changes are an inevitable part of MR research and, without quality assurance protocols, can jeopardize studies. Purpose: To evaluate changes in T1 relaxation time by inversion recovery (IR) and variable flip angle (VFA) measurements on a 3T system that underwent an "everything but the magnet" upgrade. Study Type: Longitudinal. Phantom: An International Society of Magnetic Resonance in Medicine / National Institute of Standards and Technology (ISMRM/NIST) system phantom with repeated measurements across multiple ( n = 3) days. Field Strength/Sequence: T1 IR, VFA at 3T. Assessment: The T1 measurements by IR and VFA were compared with the nuclear magnetic resonance (NMR) measurements, which constitute the known values for the ISMRM/NIST system phantom, to determine the measurement error. Statistical Tests: Descriptive. Results: The T1 VFA measurement errors were distributed around zero (–15% to +10%) on the original system and then the errors were distributed entirely above zero post‐upgrade (+5% to 30%). The T1 IR results had a dramatic increase in error distribution (±5% original, ±20% post‐upgrade) prior to the identification of signal saturation as an issue. Once the signal saturation was accounted for, the T1 IR errors decreased to ±10% post‐upgrade. Data Conclusion: The T1 VFA measurement differences between the original and post‐upgrade systems can be entirely attributed to contributions from B1 . The T1 IR measurements demonstrate the need for quantitative quality assurance (QA) processes. The site under study passed the QA protocols in place, which did not identify the increased T1 error, nor the signal saturation issue. To improve on this study, we would make systematic, quantitative measurements at intervals less than a year and following any hardware or software upgrade. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019. J. Magn. Reson. Imaging 2019;50:1948–1954.